Volume 1: Advances in Control Design Methods; Advances in Nonlinear Control; Advances in Robotics; Assistive and Rehabilitation 2018
DOI: 10.1115/dscc2018-8980
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Control Approach for Automated HEV and BEV With Short-Horizon Preview Information

Abstract: The interest in autonomous electrified vehicles has rapidly increased in recent years. In this paper, a speed trajectory generation method based on speed and road grade preview over a short horizon is presented, to improve energy efficiency of the autonomous power split HEV and BEV. The speed trajectory is generated by minimizing the required cumulative over the the horizon wheel power, including regenerative power. We confirm by simulations that the generated speed profiles improve MPG (or MPGe) even though o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In [20][21][22][23], MPC is designed using short-term prediction and it has been confirmed that, to a certain degree, this method is effective to improve energy efficiency. However, the computational burdens depending on the several important factors in MPC such as sampling-time and length of the prediction time were not analyzed thoroughly.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In [20][21][22][23], MPC is designed using short-term prediction and it has been confirmed that, to a certain degree, this method is effective to improve energy efficiency. However, the computational burdens depending on the several important factors in MPC such as sampling-time and length of the prediction time were not analyzed thoroughly.…”
Section: Literature Reviewmentioning
confidence: 95%
“…where t f corresponds to the entire duration of the trip. We remark that to compute such a globally optimal solution based on (20), the reference speed v r over the entire trip must be known a priori. This may not be as practical as the assumption of being able to predict v r for a short time horizon in the proposed receding-horizon optimization strategy (9).…”
Section: Alternative Energy Efficiency Optimization Approaches For Co...mentioning
confidence: 99%
“…We use a dynamic programming (DP) algorithm [32] to solve (20), where the constraints (9c)-(9e) are handled through penalties.…”
Section: Alternative Energy Efficiency Optimization Approaches For Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Short-range preview information and Model Predictive Control (MPC) are used in [12] to control the vehicle speed while satisfying following-distance and speed constraints. Also, the approach proposed in [13] also optimizes the speed trajectory over a short horizon, i.e., 7 sec, using short-range preview information to minimize the cumulative wheel power consumption. Parametric optimization of a feedback-based vehicle speed controller to improve fuel economy is presented in [14].…”
Section: A Literature Reviewmentioning
confidence: 99%